Implementation of E-SAKIP Policy in Improving the Performance of State Civil Apparatus in Sleman Regency during the Pandemic - Inggi Miya Febty; Suswanta Suswanta (Universitas Sultan Ageng Tirtayasa, 2022)
This study aims to analyze the implementation of the E-SAKIP Policy in Improving the Performance of the State Civil Apparatus in Sleman Regency during the Pandemic using four components of policy implementation, namely on target, government performance, Human Resources and Communication between Government Agencies implementing the Government Agency Performance Accountability System (SAKIP). which is integrated with the strategic planning system, budget system and government accounting system contained in the Indonesian Presidential Regulation Number 29 of 2014 concerning SAKIP. The research method uses a qualitative descriptive approach. The data collection technique was carried out using the Sleman Regency E-Sakip application data and then Captured through the Ncapture feature in Nvivo 12 Plus to see the implementation of policies in the E-Saki application. The results showed that the implementation carried out by the Sleman district through E-Sakip had been going well even though in the midst of a pandemic the program was running on target. Sleman Regency is one of the districts that received Good accreditation in carrying out performance through E-Sakip. the existence of E-Sakip can have an impact on increasing the performance of the implementation of public policies, programs and activities as well as budget absorption in accordance with the target.